Governança na gestão da Cooperativa Primavera (COOPRIMA) – Estado do Pará - RODRIGUES, José Vanderlande de Lima (2021)
The Master's Thesis aimed to assist in the development of the governance manual in the management of the Primavera Family Farmers and Small Rural Producers Cooperative - COOPRIMA, in the state of Pará, in support of the process of building its self-management. For this, it diagnosed how the current dynamics adopted in its management processes contribute or not to promote the integration and cooperative education of associated family farmers, in order to encourage them to participate in decision-making processes, with equity and transparency, in the search for deepening of self-management. During the dissertation, a participatory action plan was developed, using the action research methodology, to identify and detail the actions, instruments and governance channels for effective use and that, in fact, help for the self-management of the cooperative. This stage of the research was supported by authors such as Singer, Pinho, Schneider, Buttenbender, et al, and Sabourin, in order to verify the emergence of the cooperative philosophy and its importance for family farming and solidarity economy in Brazil. It was also sought to answer how changes in the governance of management in popular cooperatives influence self-management processes? COOPRIMA would be practicing a form of resistance, an alternative to being an appendix to the capitalist company, in which the supposedly self-managed work would end up being functional to the accumulation, by the flexibility in the use of the workforce, without formal salaries with cost reduction, increased profitability and competitiveness of the mining company? Issues analyzed based on the theoretical framework of researchers Gaiger, Gallo, Pinto e Reisdorfer, Chaddad and Iliopoulos, Eid and Chiariello, Reis, Singer and Becker and Dallabrida. Action research was used as a method for the investigation, anchored in Thiollent, as it is a type of social research with an empirical basis, where interaction and exchange of knowledge between the cooperative family farmers and the researcher took place, enhancing the role of the cooperative workers, in the search for solving or solving the problems found in the diagnosis. Then, an action plan was drawn up, which ended with the COOPRIMA good governance practices manual, which is intended to be a reference to good governance practices in the management of popular cooperatives.